2015
DOI: 10.1007/s10971-015-3742-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seed layer and crystallization process on crystal orientation and properties of NKBT thin films

Abstract: Lead-free (Na 0.85 K 0.15 ) 0.5 Bi 0.5 TiO 3 (NKBT) piezoelectric thin films were fabricated via an aqueous solgel method on Pt(111)/Ti/SiO 2 /Si substrates. The thin films, with and without Pb 0.8 La 0.1 Ca 0.1 Ti 0.975 O 3 seed layer, were obtained by single-crystallization and multiple-crystallization processes. The NKBT thin films derived by multiple-crystallization process exhibited better single perovskite structure, and the films with PLCT seed layers were well crystallized with high (100) orientation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…15,16 Amongst lead-free ferroelectric materials, sodium bismuth titanate (Bi 0.5 Na 0.5 TiO 3 ) is considered one of the most promising materials due to its strong ferroelectricity (P r = 38 µC/cm 2 ) at room temperature and high piezoelectric performance, especially the Bi 0.5 K 0.5 TiO 3 modified morphotropic phase boundary (MPB) solid solution 0.8Bi 0.5 Na 0.5 TiO 3 −0.2Bi 0.5 K 0.5 TiO 3 . 17,18 To improve energy storage, most researchers have used ion doping to enhance the properties of the films. Chen et al investigated the (1-x)Bi 0.5 (Na 0.8 K 0.2 ) 0.5 TiO 3 -xSrZrO 3 thin films and found that the films had excellent performance (W rec = 34.69 J/cm 3 , η = 59.32%) at x = 0.15.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Amongst lead-free ferroelectric materials, sodium bismuth titanate (Bi 0.5 Na 0.5 TiO 3 ) is considered one of the most promising materials due to its strong ferroelectricity (P r = 38 µC/cm 2 ) at room temperature and high piezoelectric performance, especially the Bi 0.5 K 0.5 TiO 3 modified morphotropic phase boundary (MPB) solid solution 0.8Bi 0.5 Na 0.5 TiO 3 −0.2Bi 0.5 K 0.5 TiO 3 . 17,18 To improve energy storage, most researchers have used ion doping to enhance the properties of the films. Chen et al investigated the (1-x)Bi 0.5 (Na 0.8 K 0.2 ) 0.5 TiO 3 -xSrZrO 3 thin films and found that the films had excellent performance (W rec = 34.69 J/cm 3 , η = 59.32%) at x = 0.15.…”
Section: Introductionmentioning
confidence: 99%